(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study evaluated the market acceptability and consumer perception of Tofu Goodies, an innovative plant-based tofu nugget enterprise paired with signature homemade sauces in Barangay Paciano Rizal, Bay, Laguna. Using a quantitative descriptive-correlation design, data were gathered from 289 targeted snack consumers within the locality. Demographic profiling showed that the core consumer segment consists of young adults aged 18–24 (43.25%) and students (44.29%) living on a limited monthly allowance below ₱5,000 (35.99%). Market acceptability achieved a favorable overall composite mean of 3.03 on a 4-point Likert scale, with product quality scoring highest (Sub-Mean = 3.10), led by the flavor profile of the homemade sauces (x̄ = 3.15).While consumers held highly positive perceptions regarding health benefits (Sub-Mean = 3.25) and environmental sustainability (Sub-Mean = 3.07), they expressed reservations regarding sensory attribute replication (Sub-Mean = 2.77). One-Way Analysis of Variance (ANOVA) proved that market acceptability was uniform across all demographic profiles (p > 0.05), failing to reject the null hypothesis. Crucially, Pearson correlation analysis revealed a non-significant relationship between consumer perception and actual product acceptability (r = -0.0186, p = 0.7534). This mathematically demonstrates that ideological alignment with healthy or green diets does not automatically translate into real-world purchasing behavior. Intense market competition (Sub-Mean = 2.87) and limited localized storefront accessibility (Sub-Mean = 2.67) emerged as primary operational challenges. These insights informed a highly structured action plan designed to secure long-term business sustainability.